Louse-borne relapsing fever (Borrelia recurrentis infection) - Warrell, DA (Cambridge University Press, 2019)
Louse-borne relapsing fever (LBRF) is an epidemic disease with a fascinating history from Hippocrates' times, through the 6th century 'Yellow Plague', to epidemics in Ireland, Scotland and England in the 19th century and two large Afro-Middle Eastern pandemics in the 20th century. An endemic focus persists in Ethiopia and adjacent territories in the Horn of Africa. Since 2015, awareness of LBRF in Europe, as a re-emerging disease, has been increased dramatically by the discovery of this infection in dozens of refugees arriving from Africa.The causative spirochaete, Borrelia recurrentis, has a genome so similar to B. duttonii and B. crocidurae (causes of East and West African tick-borne relapsing fever), that they are now regarded as merely ecotypes of a single genomospecies. Transmission is confined to the human body louse Pediculus humanus corporis, and, perhaps, the head louse P. humanus capitis, although the latter has not been proved. Infection is by inoculation of louse coelomic fluid or faeces by scratching. Nosocomial infections are possible from contamination by infected blood. Between blood meals, body lice live in clothing until the host's body temperature rises or falls, when they seek a new abode.The most distinctive feature of LBRF, the relapse phenomenon, is attributable to antigenic variation of borrelial outer-membrane lipoprotein. High fever, rigors, headache, pain and prostration start abruptly, 2-18 days after infection. Petechial rash, epistaxis, jaundice, hepatosplenomegaly and liver dysfunction are common. Severe features include hyperpyrexia, shock, myocarditis causing acute pulmonary oedema, acute respiratory distress syndrome, cerebral or gastrointestinal bleeding, ruptured spleen, hepatic failure, Jarisch-Herxheimer reactions (J-HR) and opportunistic typhoid or other complicating bacterial infections. Pregnant women are at high risk of aborting and perinatal mortality is high.Rapid diagnosis is by microscopy of blood films, but polymerase chain reaction is used increasingly for species diagnosis. Severe falciparum malaria and leptospirosis are urgent differential diagnoses in residents and travellers from appropriate geographical regions.High untreated case-fatality, exceeding 40% in some historic epidemics, can be reduced to less than 5% by antibiotic treatment, but elimination of spirochaetaemia is often accompanied by a severe J-HR.Epidemics are controlled by sterilising clothing to eliminate lice, using pediculicides and by improving personal hygiene.